Physico-Chemical Study of Waste Water Drained by Hospital of Patna: Characteristics and Treatment of Hospital Wastewater in Patna (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Wastewaters generated from hospitals contain pharmaceuticals residues, pathogens, chemical reagents, radionuclide, and other harmful matter. The wastewater characteristics, quantity, and handling methods have not only variations among Indian cities but also with in Patna. Certain hazardous waste-water (HWW's) substances may be controlled and treatment accordingly, whereas other substances have characteristics similar to domestic waste-water. Guidelines on care of these HWWs are available at a global level. Hospitals play an important role in human well-being and other advances in medical science. Various units and service centres, depending on the operations taking place in hospitals, require large quantities of water and produce large amounts of waste water. Size (number and type of wards units), services (kitchenette, laundry and air conditioning), management policy and institutional understanding influence both the quantity and characteristics of the hospital wastewater (HWW).